Early music education with Suzuki - Thames Television, ltd.; Films for the Humanities (Firm) (Princeton, NJ : Films for the Humanities & Sciences, 1992)
"Laurie was three-and-a-half when he began learning the volin by means of the controversial Suzuki method. The program follows the child's training for two years. What is clear is that the child's skills have advanced more than his age, and that the relationship between mother and child has deepened.
Title taken from container.
Date taken from container.
Date varies: tape, c1980.
VHS format.
Music composed by Elizabeth Lane.
Keywords: d; Violin -- Methods; Violin -- Instruction and study